ON THE TOTAL VERTEX IRREGULARITY STRENGTHS OF QUADTREES AND BANANA TREES - Nurdin - (Journal of the Indonesian Mathematical Society, 2012)
pdf abstractDOI : http://dx.doi.org/10.22342/jims.18.1.107.31-36